Mud matters - Dewey, Jennifer. frey50 (New York : Marshall Cavendish, 1998)
A personal account describing various uses of mud in such activities as ritual dancing, making pottery, building villages, contructing nests, playing games, and celebrating customs.
Includes index.
Keywords: Mud -- Juvenile literature; Mud